Pulmonary artery blood flow patterns in fetuses with pulmonary outflow tract obstruction. (March 2014) - Peyvandi, S.; Rychik, J.; McCann, M.; Soffer, D.; Tian, Z.; Szwast, A.
ABSTRACT Objectives Fetuses with pulmonary outflow tract obstruction (POTO) have altered blood flow to the pulmonary vasculature. We sought to determine whether pulmonary vascular impedance, as assessed by the pulsatility index (PI), is different in fetuses with POTO compared with normal controls. Methods Branch pulmonary artery PI was evaluated in age‐matched normal control fetuses (n = 22) and 20 POTO fetuses (pulmonary stenosis n = 15, pulmonary atresia n = 5). Pulsed‐wave Doppler was performed in the proximal (PA1), mid (PA2) and distal (PA3) branch pulmonary artery. The direction of flow in the ductus arteriosus was noted. The study and control groups were compared with Student's t‐test and ANOVA. A linear mixed model evaluated the relationship between PI and ductus arteriosus flow patterns. Results There was no difference in PI between control, pulmonary stenosis and pulmonary atresia subjects at PA1 and PA2; however, there was a significant difference at PA3. Subjects with pulmonary atresia had a lower PI at PA3 than did controls (P = 0.003) and pulmonary stenosis subjects (P = 0.003). Subjects with retrograde flow in the ductus arteriosus had lower PIs in PA2 and PA3 than did those with antegrade flow (P = 0.01 and 0.005, respectively). The PI in PA3 was lower in fetuses that required prostaglandin postnatally than in those that did not (P = 0.008). Conclusions Fetuses with pulmonary atresia or severe pulmonary stenosis with retrograde flow in the ductus arteriosus have decreased PI in the distal pulmonary vasculature. Our findings indicate the capacity of the fetal pulmonary vasculature to vasodilate in response to anatomical obstruction of flow. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd